Analysis of a 10 MW recompression supercritical carbon dioxide cycle for tropical climatic conditions. (5th March 2021) - Sathish, Sharath; Kumar, Pramod; Nassar, Abdul
Graphical abstract: Highlights: 10 MW sCO2 Recompression cycle design. Design of sCO2 turbine, compressors, and recuperators. The optimal operational strategy for high ambient temperatures. Part load and off-design analysis of the sCO2 recompression cycle. Abstract: Recompression supercritical CO2 (sCO2 ) power cycles offer higher efficiencies over other sCO2 cycle configurations. This paper addresses the design of a 10 MW sCO2 recompression cycle suitable for tropical climates with a compressor inlet temperature of 45 °C and a maximum turbine inlet temperature of 565 °C to facilitate the use of conventional steel alloys. A design space analysis is carried out by incorporating individual component performance under various operating conditions. The proposed cycle uses a single two-stage axial turbine and two single-stage centrifugal compressors. The results are presented on an efficiency-net-specific work diagram showing the Pareto optimal curves for a range of recompression fractions. The optimum cycle parameters, pressure ratio, and recompression fraction are found to be 2.0 and 0.25, respectively, yielding a design point efficiency of 35%. The paper brings forth the effect of turbomachinery and heat exchangers sized for 45 °C compressor inlet temperature and 565 °C turbine inlet temperature on off-design cycle performance. The analysis is applied to develop strategies for optimally operating the recompression cycle at part load and off-design conditions.